Organisational CSR practices: employees' perceptions and impact on individual performance - Gaudêncio, Pedro (2018)
The study aims to show how organisation’s corporate ethics and social responsibility have influence on satisfaction with management and workers’ attitudes and behaviours, especially in terms of organisational commitment (OC), innovative behaviour (IB) and performance. To systematise this reality, was used a self-reported sample of 223 Portuguese individuals. Structural equation modelling (SEM) was used to test the hypotheses. On the influence on satisfaction with management, the results showed that employees value the ethical component and also workforce social responsibility practices. Concerning OC, statistical evidence was found on the influence of satisfaction with management, ethical values and also workforce practices. It was also found that OC influences IB, and that this attitude had strong positive relationships with in-role performance. The empirical evidence suggests that organisation’s corporate ethics and social responsibility are important to workers, so should be taken in account by managers and be subject of research by academics.